1965
DOI: 10.1128/am.13.3.478-485.1965
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Destruction Kinetics of a Lactic Streptococcal Bacteriophage

Abstract: The aim of the study was to elucidate the kinetics of thermal destruction of a lactic streptococcal bacteriophage, and to determine the effect of varied propagation and heating conditions on its thermoresistance. The propagation medium and temperature affect the degree of thermostability of the phage produced; higher incubation temperature enhances thermostability. The composition and reaction of the heating menstruum are also of significance. Phage thermoresistance increased significantly with the phosphate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Consequently, the suspension media used in the industry could have a protective effect on L. plantarum phages. The same result for phage suspensions in milk was reported for streptococcal (11) and Lactococcus lactis (15,47) phages. Fabrizio et al (15) reported a moderate increase in the heat resistance of Lactococcus lactis phages when whole milk was used instead of skim milk.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Consequently, the suspension media used in the industry could have a protective effect on L. plantarum phages. The same result for phage suspensions in milk was reported for streptococcal (11) and Lactococcus lactis (15,47) phages. Fabrizio et al (15) reported a moderate increase in the heat resistance of Lactococcus lactis phages when whole milk was used instead of skim milk.…”
Section: Discussionsupporting
confidence: 82%
“…These phages have been characterized mainly by their genomes (8,10,14,26,27,39,49,52) and by their interactions with sensitive bacterial strains (8,27,39,49); however, data on their chemical and thermal resistance are scarce. In contrast, data have been reported on thermal and chemical resistance of phages infecting Lactococcus (2,5,11,15,20,43,47,51,53), Streptococcus thermophilus (3), Lactobacillus casei and Lactobacillus paracasei (7), Lactobacillus delbrueckii (44), and Lactobacillus helveticus (45).…”
mentioning
confidence: 99%
“…Several other studies also noted that the medium components of phage solution could affect the thermal stability of phages ( Fabrizio et al, 1999 ; Sua’/rez and Reinheimer, 2002 ; Quiberoni et al, 2003 ; Briggiler Marco et al, 2009 ). It was reported that reconstituted non-fat dry skim milk is more protective than De Man, Rogosa and Sharpe (MRS) broth against thermal inactivation of some dairy phages ( Daoust et al, 1965 ; Quiberoni et al, 2003 ). Whole milk provides better thermal protection than skim milk for Lactococcus lactis phages ( Fabrizio et al, 1999 ).…”
Section: Resultsmentioning
confidence: 99%